Micro Business Segmentation Using Categorical Test Approach In Supporting Sales Network In East Java Indonesia - Che Zalina bt Zulkifli; I Putu Artaya; Wasana Boonsong; Sengguruh Nilowardono (LPPM of NAROTAMA UNIVERSITY, 2022)
The main purpose of this research is to see or position the region in East Java, especially micro-enterprises by segmenting their products. There are five effective areas in East Java which are well-known centers of micro-enterprises, i.e Mojokerto, Pasuruan, Malang, Gresik and Lumajang with their local wisdom products. There are 160 micro business actors in the five regions of East Java. Where their products have the opportunity to be developed into mainstay products in the province of East Java. Based on the results of the Categorical test, an overview of the test results is obtained, i.e: for micro-enterprises in Malang and Gresik they have the same character (dimension 1, i.e: innovation, product attractiveness, product originality, raw materials and environmentally friendly) both management and products so that because they have similarities , the two regions deserve to develop a joint business in a sales network. As for dimension 2 (selling value, market value, quality and market opportunity) micro-enterprises in Pasuruan, Malang and Gresik can form a group together in the sales network in facing market opportunities and increasing sales. Whereas micro-enterprises in Lumajang city (are in a neutral segment (not dimension 1 and not dimension 2), micro-enterprises in Lumajang district may compete with four other cities in fighting for market opportunities, both locally and globally because in the Categorical test the position of micro-enterprises Lumajang is categorized as having a special character and is different from the other four cities, i.e Malang, Gresik, Mojokerto and Pasuruan, so that only micro-enterprises in Lumajang district may not participate in the sales network.